Low concentrations of acetylcarvacrol induce drastic morphological damages in ovaries of surviving Rhipicephalus sanguineus sensu lato ticks (Acari: Ixodidae) - Konig, Isaac Filipe Moreira; Oliveira, Marcos Vinícius Silva; Gonçalves, Raquel Romano Palmeira; Peconick, Ana Paula; Thomasi, Sérgio Scherrer; Anholeto, Luís Adriano [UNESP]; Lima-de-Souza, José Ribamar; Camargo-Mathias, Maria Izabel [UNESP]; Remedio, Rafael Neodini (Elsevier, 2020)
Rhipicephalus sanguineus sensu lato (s. l.) ticks are targets of acaricidal treatments due to their great veterinary and medical importance. Acetylcarvacrol stands out as a promising acaricidal substance for its increased biocidal activity and stability. Additionally, its toxicity to mammals is reduced when compared to the parent molecule, carvacrol. The present study aimed to evaluate the effects of acetylcarvacrol on the morphology of ovaries of engorged R. sanguineus s. l. ticks. The animals were subjected to the Adult Immersion Test to calculate the lethal concentrations (LC50 and LC90) of acetylcarvacrol. Subsequently, the surviving ticks were dissected for collection of the ovaries. The samples were processed through routine histological techniques. The histological sections were stained with hematoxylin and eosin, bromophenol blue (protein detection) and PAS (polysaccharide detection). The alterations found in the ovaries were evaluated by morphometric and semiquantitative analysis. The LC50 and LC90 were 17.805 and 26.164 μL/mL, respectively. The most severe morphological alterations were disappearance of the female germ cells (oocytes), nucleolus vacuolization, thicker and irregular chorion, and decrease in size of the oocytes. Also, the content of proteins and carbohydrates in the oocytes were heavily affected by the chemical, as evidenced by a non-homogeneous staining pattern. The group exposed to the highest concentration of acetylcarvacrol (20 μL/mL) exhibited a statistically greater score in the semiquantitative analysis when compared to the other groups. The morphological changes in the ovaries may reduce the ticks' offspring production or generate descendants that will struggle to carry out essential biochemical processes during their lives. Thus, acetylcarvacrol may be a promising alternative to control tick infestation by impairing the reproduction of this parasite.
Keywords: Brown dog tick; LC50; Ovary; Tick control; Toxicity